Towards a mid-infrared L band up-conversion interferometer: first on-sky sensitivity test on a single arm. Issue 3 (14th March 2019) - Lehmann, Lucien; Grossard, Ludovic; Delage, Laurent; Reynaud, François; Chauvet, Mathieu; Bassignot, Florent; Martinache, Frantz; Morand, Frédéric; Rivet, Jean-Pierre; Schmider, François-Xavier; Vernet, David
Abstract: We report on the first on-sky sensitivity test on a single arm of the Astronomical Light Optical Hybrid Analysis (ALOHA) instrument, an uncooled up-conversion interferometer in the L band (3.5 μ m). Despite a low coupling efficiency (in the range of 1 per cent) between the 1-m class telescope and our instrument, we detect a magnitude L mag = 2.8 star with a signal-to-noise ratio SNR = 2.7 over a 30 min integration time and with a spectral resolution λ/Δλ = 100. As the ALOHA project aims to shift light from the L band to the near-infrared, the use of very low loss silica optical fibres is an important step towards fibre-linked very long-baseline interferometry in the mid-infrared.